A scanning electron and light microscopy study of the red tide dinoflagellate Gymnodinium sp. from False Bay, South Africa - Dawood, Abeda (Department of Biological Sciences, 2017)
A previously unrecorded red tide dinoflagellate bloomed in False Bay during 1988 and 1989, causing faunal mortalities as well as eye, nose and lung irritations to bathers and fishermen. Light microscopy and scanning electron microscopy was used in an attempt to identify this species which shared certain features with the following species: (a) Gymnodinium nagasakiense Takayama et Adachi, the western Pacific species, with which it has the external morphology in common, (b) Gyrodinium aureolum Hulburt, the North Atlantic species which is common in northern European and eastern USA waters, with which it shares the cell shape and the nucleus position, (c) Ptychodiscus brevis (Davis) Steidinger, the north American species, which has a similar toxic effect. Ptychodiscus brevis differed from the False Bay organism in several aspects, including cell contour, the possession of an apical protrusion, and the toxins of P. brevis are lipid soluble whereas the toxins of Gymnodinium sp. are water soluble. The local species was morphologically similar to Gymnodinium nagasakiense but had the nucleus in a different position. G. nagasakiense has the nucleus in the left side of the cell, whereas in the local species the nucleus was situated sub-centrally to centrally. It is concluded that Gynnodinium sp. was most similar to Gyrodiniun aureolum but differed in their toxic effects. The epithet Gyrodiniun cf. aureolum is suggested although the local species may be a new species. Further research using DNA contents and transmission electron microscopy are needed to clarify this problem.